2013
DOI: 10.1016/s0034-7094(13)70210-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Nitrous Oxide on Controlled Hypotension During Low Flow Anesthesia

Abstract: By using dexmedetomidine instead of nitrous oxide in low flow isoflurane anesthesia, we attained desired MAP levels, sufficient anesthesia depth, hemodynamic stability and safe inspiration parameters. Dexmedetomidine infusion with medical air-oxygen as a carrier gas represents an alternative anesthetic technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The study of Barçın et al revealed that patients had desired MAP levels, hemodynamic stability and safe inspiration parametres by using dexmedetomidine instead of nitrous oxide in LFA. They concluded that dexmedetomidine infusion with medical air-oxygen as a carrier gas represents an alternative anesthetic technique [20].…”
Section: Discussionmentioning
confidence: 99%
“…The study of Barçın et al revealed that patients had desired MAP levels, hemodynamic stability and safe inspiration parametres by using dexmedetomidine instead of nitrous oxide in LFA. They concluded that dexmedetomidine infusion with medical air-oxygen as a carrier gas represents an alternative anesthetic technique [20].…”
Section: Discussionmentioning
confidence: 99%